A community outbreak of Legionnaires’ disease in Geneva, Switzerland, June to September 2017 (Swiss Medical Weekly, 2018)
PURPOSE Eight confirmed cases of Legionnaires’ disease were identified at the Geneva University Hospitals between 28 July 2017 and 02 August 2017, leading to a detailed outbreak investigation. METHODS Legionnaires’ disease cases were defined according to Swiss and European (ELDSNet) consensus guidelines. An outbreak investigation task force was put in place. Patients were interviewed, when feasible, with a standard questionnaire. A Legionella pneumophila urinary antigen test was performed in all cases. Lower respiratory tract (LRT) specimens were collected for culture, polymerase chain-reaction (PCR) assay, monoclonal antibody subtyping and sequenced-based typing (SBT). Multiple environmental samples were collected. Case geographical mapping was performed and local meteorological data were obtained. RESULTS Thirty-four confirmed cases of Legionnaires’ disease were identified between 20 June 2017 and 16 September 2017, including 28 patients living in the Canton of Geneva and 6 cases in neighbouring cantons and France. The case fatality rate was 8.8%. The urinary antigen test was positive in 32/34 (94.1%) cases. Among the 17/34 (50%) cases with available LRT specimens, 8 (47.1%) were culture/PCR positive, 5 (29.4%) were PCR positive only, and 4 (23.5%) were culture/PCR negative. Monoclonal antibody subtyping and SBT on 12 samples allowed subtype identification of 8 samples, with a predominance of L. pneumophila serogroup-1 subtype-France/Allentown ST23 among clinical isolates. A specific city area was identified as a possible outbreak epicentre in 25/34 (73.5%) cases, although molecular analysis of clinical and environmental specimens revealed heterogeneous subtypes of L. pneumophila. CONCLUSIONS In this largest documented outbreak of Legionnaires’ disease in Switzerland, we report prompt outbreak identification, leading to timely initiation of a detailed, well-orchestrated clinical and epidemiological investigation.